A quantitative study to evaluate the controls and accountability measures in place to alleviate the leadership and governance challenges impacting the realization of the National Health Insurance (NHI) in South Africa - Samuel Vuyo Mokoena; Panjasaram Naidoo (Health Research Policy and Systems)
Abstract Objectives Governance and leadership are regarded as the most crucial aspects in delivering quality health care, and yet they are arguably the most complex functions of any health system. The objective of the study was to investigate the structural problems affecting the implementation of the National Health Insurance (NHI) and address the challenges affecting the NHI building blocks. Further objective of the study was to evaluate if there were appropriate controls and accountability measures in leadership and governance to inform the development of a workable model for the implementation of the NHI in South Africa. Design A quantitative study was undertaken to interrogate the structural problems affecting the implementation of the NHI by seeking to address the challenges affecting the NHI building blocks. Setting and participants The study was undertaken with participants who are decision-makers and/or contribute to the health sector reforms in South Africa in the realization of the NHI. Main outcome The main outcome of the study was to determine the requisite interventions to deal with challenges that affect governance and/or leadership functions in the implementation of the NHI. Methods The questionnaire was distributed via SurveyMonkey over a period of 2 months, and the data were analysed using R Statistical computing software of the R Core Team, 2020, version 3.6.3. The results were presented in the form of descriptive and inferential statistics. Results The study found that the success to implement NHI needs to be supported by clarity and commitment to specific policy fundamentals aimed at improving efficiency, stakeholder participation, and accountability. This imperative remains very much in doubt since the different occupations hold different views about the progress made in the implementation of the NHI across the governance and leadership functions. Conclusions The study confirmed the interrelatedness of the subthemes identified for the governance and leadership construct and pointed to the importance of sharpening policy development and implementation approaches in collaboration with all relevant stakeholders. Protocol registration The Ethics approval reference number is HSSREC 00002565/2021.